Secondary School Teachers’ Beliefs about Grammar Teaching in Ethiopia - Kahsay, Mulugeta Teka (Bahir Dar Journal of Education, 2020)
This study intended to investigate EFL teachers’ beliefs about direct/explicit and indirect/implicit grammar instruction. A simple random sampling technique was applied to select 396 secondary school EFL teachers among those who were pursuing their M.A. studies in the summer program of five universities. Among these, 348 participants responded to a questionnaire consisting of 21 items adapted from Jean and Simard (2011) and from Borg and Burns (2008). Then an exploratory factor analysis was applied, and the test determined only 15 items that would address the two types (direct and indirect) of grammar instruction. The results indicated that the teachers believed that implicit grammar teaching was viable, but they favored the explicit grammar teaching in their context. The paired sample t-test result, t (347) = 5.655; p< .05; Cohen’s d = .95), revealed that the teachers had significantly stronger beliefs in the direct/explicit grammar instruction than in indirect/implicit grammar instruction. The two-way ANOVA results revealed that the participants’ beliefs about direct grammar instruction significantly differed (F (2, 346) = 14.120; p < .05, partial eta square= .076) as a function of teaching experience in favor of the group of the most experienced teachers, but their belief about indirect grammar instruction did not differ as a function of both teaching experience and level of school they taught. The findings suggest a possible tension and conflict between belief and practice in the grammar instructional process, given the strong impact of teacher beliefs on teaching behaviors as the literature confirmed. Recommendations have also been included considering the findings of the study.